Pengembangan Soal Numerasi Berbantuan Platform ESD-Mathpath untuk Mengukur Kemampuan Berpikir Kritis Siswa SMP - Muhammad Mayvanda Syahrun Adzim (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
In the Merdeka Curriculum, one of the emphasized learning systems is critical thinking. Critical thinking is closely related to numeracy-oriented problems. The Minimum Competency Assessment (MCA) in Numeracy serves as a tool to measure students’ thinking abilities in applying mathematical concepts and procedures in real-life contexts. However, in practice, there are still many obstacles in its implementation due to the limited availability of MCA-standardized questions and the lack of students’ habituation in solving numeracy problems. This study aims to determine the validity, practicality, reliability, and effectiveness of numeracy questions assisted by the ESD-Mathpath platform that were developed. This research employed a Research and Development (R&D) method using the 4D Thiagarajan model, which consists of four stages: define, design, development, and disseminate. The subjects of this study were 75 eighth-grade students of SMP Negeri 3 Jember. The data were analyzed quantitatively using Rasch analysis assisted by Ministep software. The results showed that the numeracy test instrument was declared valid after being validated by validators, with a Va score of 3.65. The practicality aspect was based on the item validity results, which indicated that all test items fulfilled at least one validity criterion. The reliability analysis showed an excellent category with an item reliability score of 0.97. The effectiveness analysis conducted at the dissemination stage indicated an effective category with a score of 73.3. Based on these results, it can be concluded that the numeracy question package through the ESD-Mathpath platform can be used as a reference for teachers to train students’ critical thinking skills, especially in contextual mathematical problems related to their surrounding environment.
Validasi dan Finalisasi Repositori File 25 Juni 2026_Kholif Basri
Keywords: Critical thinking skill; numeracy questions; education for sustainable development (ESD); ESD-Mathpath platform